Mountain Climber System Health and GPS Tracker - Baharudin, Nur Amirul Farhan; Razali, Muhammad Anas (Evolution in Electrical and Electronic Engineering, 2025)
The project ensures climber safety by monitoring vital signs like heartbeat and temperature in real- time, enabling the early detection of emergencies. This IoT and GPS- based system provides precise tracking of climbers’ locations, aiding search and rescue operations in remote terrains. The system features a Durian ESP32, heartbeat and temperature sensors, Wi-Fi and GSM modules, and an LCD display. It transmits real-time data and track’s locations, offering climbers enhanced situational awareness. Emergency alerts are triggered via visual and SMS notifications at Blynk in case of deviations in vital signs or accidents, ensuring prompt responses. Key results include achieving 96% accuracy in heart rate and temperature monitoring, reducing alert response time to under 5 seconds, maintaining 99% reliability in remote areas, and extending device operational time to 10 hours on a single charge. Though challenges like extreme weather, signal interference, power dependency, and GPS accuracy exist, the system strengthens safety infrastructure, improving coordination for rescue operations. This project significantly enhances climber safety in hazardous mountain environments through advanced monitoring and tracking technologies.